Closure Device-Related Thrombosis After Anticoagulation With Dabigatran in Patients Undergoing Percutaneous Left Atrial Appendage Closure: Case Reports and Literature Review - Li, Xiaoye; Jin, Qinchun; Zhang, Xiaochun (Frontiers in Pharmacology, 2020)
Percutaneous left atrial appendage closure (LAAC) is an effective and safe operation strategy for stroke prevention in patients who are diagnosed with atrial fibrillation (AF) but cannot tolerate long term anticoagulation medication. We presented four rare cases of thrombosis formation on the occluder device. After the LAAC operation was successfully performed on patients they followed a course of anticoagulation with dabigatran (110mg b.i.d.), and device-related thrombosis (DRT) occurred as indicated by a transesophageal echocardiogram (TEE) during the follow-up period. Regressions were achieved after replacing dabigatran with rivaroxaban or warfarin for more than one month. No thrombosis or bleeding-related complications occurred in subsequent follow-ups.